Tanggung Gugat Konsumen Gagal Bayar dalam Perjanjian Pembiayaan Konsumen Akibat Pandemi Corona Virus Disease 2019 (Covid-19) - Sugeng Andrean (Jurist-Diction, 2021)
AbstractThroughout 2020 until earlier 2021 world is hit by pandemic known as the COVID-19 pandemic. Many sectors have the impact of this pandemic, one of which is the economic sector, especially consumer financing institutions. In Indonesia the COVID-19 pandemic has been designated as a non-natural national disaster through Presidential Decree No. 12/2020 (hereinafter referred to as Keppres 12/2020). Consumer or debitor at consumer finance companies argue that this Presidential Decree 12/2020 can be used as an excuse for force majeure so that contracts that have been made can be misled or canceled. For this reason, researchers conducted legal research to find answers to whether the COVID-19 pandemic could be used as an excuse force majeure in consumer financing contracts. In addition, researchers will also examine what legal measures can be made by consumers who fail to pay due to the COVID-19 pandemic for determining defaults in financing companies. Keywords: COVID-19 Pandemic; Force Majeure; Consumer Financing Restructuring.AbstrakSepanjang tahun 2020 hingga awal tahun 2021 ini dunia tengah dilanda pandemi virus yang dikenal dengan sebutan pandemi COVID-19. Banyak sektor mengalami dampak dengan adanya pandemi ini, salah satunya adalah sektor ekonomi khususnya lembaga pembiayaan konsumen. Di Indonesia pandemi COVID-19 telah ditetapkan sebagai bencana nasional non alam melalui Keputusan Presiden Nomor 12 Tahun 2020 (selanjutnya disebut Keppres 12/2020). Konsumen atau debitur pada perusahaan pembiayaan konsumen mendalihkan bahwa Keppres 12/2020 ini dapat dijadikan alasan force majeure sehingga kontrak yang telah dibuat dapat disimpangi atau dibatalkan. Untuk itu peneliti melakukan penelitian hukum guna menemukan jawaban apakah pandemi COVID-19 dapat dijadikan alasan force majeure dalam kontrak pembiayaan konsumen. selain itu, peneliti juga akan menelaah upaya hukum apa yang dapat dilakukan konsumen gagal bayar akibat pandemi COVID-19 atas penetapan wanprestasi pada perusahaan pembiayaanKata Kunci: Pandemi COVID-19; Force Majeure; Restrukturisasi Pembiayaan.